ANALISIS HIDRO-OSEANOGRAFI UNTUK BUDIDAYA TIRAM MUTIARA DI PERAIRAN BAUBAU - Jamilah Jamilah (Jurnal Biotek, 2015)
Community activities to perform, especially marine aquaculture farming pearl oysters around Baubau municipal waters has increased. This study aims to analyze (1). hydro-oceanographic factors for the suitability of the development of pearl oyster farming in the waters of the city of Baubau, Southeast Sulawesi (2). The capacity of the land and the production capability of land for the development of pearl oyster farming based on changes in hydro oceanographic parameters. The method used is the exploratory study using survey methods and direct measurements in the field. Data were analyzed descriptively reported in the form of Tables and Figures. The results showed that after a through analysis of hydro oseangrafi waters of Baubau then obtained the appropriate areas suitable for cultivation and pearl oyster 512.31 hectares with a capacity of 409.85 hectares of land available. pearl oyster cultivation of 40 985 units with production forecast 4391.23 tons / year or as much as 133,434.80 grains / year.